ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERSEDIAAN OBAT-OBATAN PADA PUSKESMAS MERSAM KECAMATAN MERSAM KABUPATEN BATANGHARI - Alpandi, M.; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2019)
Mersam Health Center Mersam District Batanghari District in processing data on drug supply, drugacceptance, drug use, drug demand, drug distribution is still done manually, namely by recording everyday on the stock card. Then the drug data from the stock card is recapitulated and a LPLPO (UsageReport and Drug Request Sheet) is made using Microsoft Excel to request medication to the BatanghariDistrict Pharmacy Installation. With this process, the pharmacist assistant has difficulty causing errors inthe calculation of drug stocks, making it difficult to check the drug inventory, resulting in the length of thereport and the missing documents due to improper archiving of the data and not using the database. Thepurpose and benefits of this study are to analyze and study the problems of the drug supply informationsystem at Mersam Health Center, Mersam Subdistrict, Batanghari District and produce Prototype byusing object-oriented methods and can help the drug department employees in making drug inventorydecisions, drug management treatment is easy, fast and efficient. The design of information systems inthis study uses UML (Unified Modeling Language) tools such as use case diagrams, activity diagrams,and class diagrams. This study produced a prototype drug inventory information system that can presenta drug inventory report. This prototype needs to be developed for further research so that it can beapplied by completing a data security system (security).